Prevalence and predictors of mortality in gastroschisis: a population-based study of 4803 cases in the USA. (18th May 2020) - Brebner, Alison; Czuzoj-Shulman, Nicholas; Abenhaim, Haim Arie
Abstract: Purpose: Gastroschisis is a rare congenital anomaly consisting of an abdominal wall defect resulting in extrusion of the abnormal organs. Survival of these infants exceeds 90%. Few large-scale studies have examined the predictors of mortality for these infants. Our objective was to conduct a population-based study to determine prevalence and predictors of mortality among infants born with gastroschisis. Materials and methods: We used the "Period Linked Birth-Infant Death" database to create a cohort of all births occurring between 2009 and 2013. Infants were categorized by the presence of gastroschisis, excluding infants born at <24-week gestation. Baseline maternal and newborn characteristics were compared for infants who survived and those who died. Multivariate logistic regression models were used to estimate the effect of maternal and fetal factors on mortality, while adjusting for appropriate baseline characteristics. Results: There were 4803 cases of gastroschisis, with 287 deaths. The prevalence of gastroschisis increased from 2.04 to 2.49/10, 000 births over the study period. The rate of death stayed constant at about 5.9%. We found that 38.1% of these infants died on day 0 of life. Statistically significant predictors of mortality were the presence of an additional congenital anomaly, birth weight <2500 g, prepregnancy diabetes, gestational age <34 weeks, paying out of pocket for healthcare, and maternal obesity. Conclusions: The prevalence of gastroschisis in the USA increased, yet the mortality rate remained stable. Infants born preterm <34 weeks, with birth weights <2500 g, or with an additional congenital anomaly were at the highest risk of death.